INKONSISTENSI BATAS USIA ANAK DALAM PERKARA PERWALIAN DI PENGADILAN AGAMA PERSPEKTIF KEPASTIAN HUKUM - Maharani, Vanya Faby; Kamarusdiana, Kamarusdiana; Yassardin, Yassardin (UIN Walisongo Semarang, 2024)
This paper is a normative juridical research with a statutory approach and case approach. The primary data sources are Banjarbaru Religious Court Decision Number 0026/Pdt.P/2015/PA.Bjb and Cilegon Religious Court Decision Number 09/Pdt.P/2017/PA.Clg, the Marriage Law, and the Compilation of Islamic Law. The secondary data sources are articles, journals, and other sources related to the discussion in this paper. The results of this paper found that an application for legal guardianship is submitted to the Court in order to determine who is entitled to guardianship of a child who is still a minor and not yet legally competent. In reality, even parents who are directly entitled to underage children for certain cases still apply for custodial status to the Religious Court so that there is concrete evidence or documents on this matter. There are many provisions governing children as well as guardianship, so that judges decide with different references, but still provide certainty to the case submitted because there is a law that regulates it clearly. In certain cases related to children's property or inheritance rights, the judge has other considerations related to this matter.